The role of gibberellin synthase gene VvGA2ox7 acts as a positive regulator to salt stress in Arabidopsis thaliana - Huimin Gou; Shixiong Lu; Guojie Nai; Weifeng Ma; Jiaxuan Ren; Lili Guo; Baihong Chen; Juan Mao (BMC Plant Biology)
Abstract Background Soil salinity is an important environmental component affecting plant growth and yield, but high-salinity soils are a major constraint to the development of the grape industry. Previous studies have provided lines of evidence that gibberellins (GAs) play a significant regulatory role in plant responses to salt stress. However, it remains unclear whether GA2ox, a key enzyme that maintains the balance of bioactive gibberellins and intermediates in plants, is involved in the mechanism of salt stress tolerance in grapes. Results In this study, we found that GA2ox7 positively modulates salt stress via its ectopic expression in Arabidopsis thaliana. The GA2ox7 gene cloned from grape was a hydrophilic protein, its CDS length was 1002 bp. Besides, VvGA2ox7 protein contained DIOX_N and 2OG-FeII_Oxy domains and was localized at the nucleus and cytoplasm. Yeast two-hybrid (Y2H) showed VvARCN1, VvB5R, VvRUB2, and VvCAR11 might be potential interaction proteins of VvGA2ox7. Compared with the wild type, overexpression of VvGA2ox7 in Arabidopsis thaliana enhanced antioxidant enzymatic activities and proline, chlorophyll, and ABA contents, and decreased relative electrical conductivity, malondialdehyde, and GA3 contents. Moreover, overexpression of VvGA2ox7 positively regulated the expression of salt stress response genes (KAT1, APX1, LEA, P5CS1, AVP1, CBF1), indicating that the VvGA2ox7 overexpression improved the salt stress tolerance of plants. Conclusions Taken together, this investigation indicates that VvGA2ox7 may act as a positive regulator in response to salt stress and provide novel insights for a deeper understanding of the role of VvGA2ox7 in grapes.